Should we encourage the use of robotic technologies in complicated diverticulitis? Results of systematic review and meta-analysis - Panin, S. I.; Nechay, T. V.; Sazhin, A. V.; Tyagunov, A. E.; Shcherbakov, N. A.; Bykov, A. V.; Melnikov-Makarchuk, K. Yu; Yuldashev, A. G.; Kuznetsov, A. A. (Frontiers in Robotics and AI, 2023)
Introduction: Complicated diverticulitis is a common abdominal emergency that often requires a surgical intervention. The systematic review and meta-analysis below compare the benefits and harms of robotic vs. laparoscopic surgery in patients with complicated colonic diverticular disease. Methods: The following databases were searched before 1 March 2023: Cochrane Library, PubMed, Embase, CINAHL, and ClinicalTrials.gov. The internal validity of the selected non-randomized studies was assessed using the ROBINS-I tool. The meta-analysis and trial sequential analysis were performed using RevMan 5.4 (Cochrane Collaboration, London, United Kingdom) and Copenhagen Trial Unit Trial Sequential Analysis (TSA) software (Copenhagen Trial Unit, Center for Clinical Intervention Research, Rigshospitalet, Copenhagen, Denmark), respectively. Results: We found no relevant randomized controlled trials in the searched databases. Therefore, we analyzed 5 non-randomized studies with satisfactory internal validity and similar designs comprising a total of 442 patients (184 (41.6%) robotic and 258 (58.4%) laparoscopic interventions). The analysis revealed that robotic surgery for complicated diverticulitis (CD) took longer than laparoscopy (MD = 42 min; 95% CI: [-16, 101]). No statistically significant differences were detected between the groups regarding intraoperative blood loss (MD = −9 mL; 95% CI: [–26, 8]) and the rate of conversion to open surgery (2.17% or 4/184 for robotic surgery vs. 6.59% or 17/258 for laparoscopy; RR = 0.63; 95% CI: [0.10, 4.00]). The type of surgery did not affect the length of in-hospital stay (MD = 0.18; 95% CI: [–0.60, 0.97]) or the rate of postoperative complications (14.1% or 26/184 for robotic surgery vs. 19.8% or 51/258 for laparoscopy; RR = 0.81; 95% CI: [0.52, 1.26]). No deaths were reported in either group. Discussion: The meta-analysis suggests that robotic surgery is an appropriate option for managing complicated diverticulitis. It is associated with a trend toward a lower rate of conversion to open surgery and fewer postoperative complications; however, this trend does not reach the level of statistical significance. Since no high quality RCTs were available, this meta-analysis isnot able to provide reliable conclusion, but only a remarkable lack of proper evidence supporting robotic technology. The need for further evidence-based trials is important.